Water Distribution Efficiency for Lining Construction Of Telabah Aya in Subak Irrigation System, Badung Regency - AS., I Made Hendra Udayana; Tika, I Wayan; Arthawan, I Gusti Ketut Arya (Jurnal BETA (Biosistem dan Teknik Pertanian), 2022)
The efficiency of distribution becomes the basis in the distribution of irrigation water in subak irrigation systems. The condition of the distribution efficiency in telabah aya is influenced by the physical condition of the canal, particularly depending on the type of lining canal used. The application of lining canals in Subak, Badung Regency is proof that it has a lot of influence in irrigation distribution. The information on thedistribution efficiency is required for the lining of telabah as a basic reference value in irrigation water distribution. The method used in this study is quantitative surveys and lining observations, and direct measurements of debit variables in telabahaya. Lining observations are based on 30 objects with lining canals in Badung regency. The flow speed measurement was carried out using buoy instruments. The size of the flow cross-section was measured with a roll meter. Measurement of water discharge wasperformed upstream and downstream of telabah aya to get the amount of initial discharge and final discharge as a basis for determining the efficiency of distribution. The lining canal used in telabah aya in Badung Regency is 77% types of stone and l-shapeconcrete as much as 23%. The value of distribution efficiency for telabah aya with stone lining by 75.20% and l-shape concrete type by 93.07%. This difference in efficiency value is due to the lining canal conditions in each telabah aya.